2017
DOI: 10.1002/fsn3.543
|View full text |Cite
|
Sign up to set email alerts
|

Orange‐fleshed sweet potato (Ipomoea batatas) composite bread as a significant source of dietary vitamin A

Abstract: Refining food recipes with orange‐fleshed sweet potato (OFSP) has the potential to improve dietary intake of vitamin A. The objectives of this study were to utilize OFSP in the development of two composite bread types and to assess their contribution to dietary intake of vitamin A using the dietary reference intake of lactating mothers. Two composite OFSP–wheat flour bread recipes—vita butter bread and vita tea bread—were developed by incorporating 46% OFSP puree in existing 100% wheat flour bread recipes cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 10 publications
(20 reference statements)
1
20
0
Order By: Relevance
“…Generally, compositing OFSP with cassava for gari production resulted in an increase in the amount of β‐carotene in the composite gari (Table ). The results agree with related studies where OFSP flour and puree were composited with wheat flour for composite bread production (Awuni et al, ; Nzamwita et al, ). Increases in β‐carotene as OFSP amount is increased may primarily be due to the concentration effect of the OFSP in the cassava dough.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Generally, compositing OFSP with cassava for gari production resulted in an increase in the amount of β‐carotene in the composite gari (Table ). The results agree with related studies where OFSP flour and puree were composited with wheat flour for composite bread production (Awuni et al, ; Nzamwita et al, ). Increases in β‐carotene as OFSP amount is increased may primarily be due to the concentration effect of the OFSP in the cassava dough.…”
Section: Resultssupporting
confidence: 92%
“…This design was chosen due to its robustness for optimization studies involving many responses and at least two factors. The effect of different proportions of OFSP ranging from 10 to 30% was chosen based on similar studies for composite bread (Nzamwita, Gyebi, & Minnaar, ) and composite gari cost implications (Awuni et al, ). The FD from 1 to 3 days was selected based on the traditional duration of fermentation in Ghana.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Potato Center (CIP) has gained considerable experience by pilot work in Rwanda and has partnered with companies manufacturing and marketing bakery products in which 20%-45% of wheat flour has been replaced by OFSP puree (boiled and mashed roots). Experience across many SSA countries has shown that with the current price of sweet potato roots, it is economically advantageous to use OFSP puree as a wheat substitute instead of OFSP flour (Awuni, Alhassan and Amagloh, 2017). Moreover, products made using OFSP puree are highly acceptable to consumers.…”
mentioning
confidence: 99%
“…Weighed intakes of sweet potato breads high in β-carotene were evaluated in Ghanaian lactating women. These breads provided an estimated 1.9 and 3.3 mg β-carotene/d, meeting 12% and 21% of estimated requirements ( 166 ). Other VA-rich foods, including red palm oil and small fish, have been analyzed for their potential to contribute to VA intakes in pregnant and lactating women ( 167 , 168 ).…”
Section: Resultsmentioning
confidence: 99%